Silver-catalyzed decarboxylative alkynylation of α,α-difluoroarylacetic acids with ethynylbenziodoxolone reagents - Chen, Fei; Hashmi, A. Stephen K. (Organic letters, 2016)
A decarboxylating alkynylation of α,α-difluoroarylacetic acids with ethynylbenziodoxolone reagents is reported. AgNO3 serves as the catalyst and K2S2O8 as the oxidant. A series of functional groups were tolerated, and moderate to good yields were obtained.
Gesehen am 20.09.2017